Identifying Morpho-Physiological Characteristics Associated with Drought Tolerance in Selected Chikpea Germ Plasm in Nakuru and Baringo Counties, Kenya - Kirui, Grace J.; Njoka, Fredrick M. (My University, 2013)
This paper examines the morpho-physiological characteristics of chickpea associated with drought tolerance based on a study of selected chickpea lines under field conditions in Nakuru and Baringo counties in Kenya. Drought has been spreading to more land in Kenya over the years due to climatic change attributed to global warming. Chickpea being drought resistant can act as a cereal-legume relay crop in dry highlands during the short rains as it improves soil fertility and conserves moisture. But currently there are no lines released for commercial production in Kenya, hence there is need to introduce and evaluate several lines to identify those that can do well in dry lands of Kenya. This study therefore screened several chickpea genotypes to identify and select drought tolerant lines with associated morpho-physiological characteristics under field conditions and determined their heritability. The study was conducted in two sites, at Koibatek-Farmers Training Centre for two seasons (during the short and long rains) and in KEPHIS-Lanet for one season (long rains). A mini core collection of 30 lines from ICRISAT was evaluated in the two sites in a Randomised Complete Block Design (RCBD), replicated twice. Parameters that were measured included phenological growth stages, yield (Kg/ha) and its components which included number of pods/plant, plant height (cm), plant spread (cm), biomass (Kg/ha), harvest index (HI). All data collected were analyzed using Analysis of Variance (ANOVA) using Genstat and means separated by Duncan Multiple Range Test (DMRT) at (P=0.05). The morphological traits associated with drought tolerance due to their direct contribution to yield included biological mass, days to physiological maturity, days to 50% flowering and % DTE. These traits could be of interest in improving chickpea since they could be genetically manipulated or improved due to their high genetic contribution to their phenotypic traits. There is need for further screening and breeding of the selected lines for drought tolerance.
Keywords: Morpho-physiological Characteristics; Drought Tolerance; Chikpea Germ Plasm; Kenya